1995
DOI: 10.1254/jjp.67.59
|View full text |Cite
|
Sign up to set email alerts
|

Antisecretory and Antiulcer Effects of YM020, a New H+,K+-ATPase Inhibitor, in Rats and Dogs

Abstract: We examined the effects of YM020 (3-cyanomethyl-2-methyl-8-[(3-methyl-2-butenyl)oxy]-imidazo[1,2-a]pyridine), a novel H+,K+-ATPase inhibitor, on gastric acid secretion and experimental gastroduodenal lesions in rats and dogs. Intraduodenal, subcutaneous and oral YM020 inhibited basal gastric acid secretion in pylorus-ligated rats with ED50 values of 9.1, 9.1 and 9.5 mg/kg, respectively. Oral pretreatment with YM020 5 hr before ligation still suppressed acid secretion, with a potency a little less than that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…After showing that bosentan inhibited WIRS‐stimulated acid secretion, they concluded that the antisecretory properties of bosentan are likely to be responsible for prevention of gastric damage 23 . This conclusion would make bosentan about three times less potent than omeprazole in attenuating gastric lesions in WIRS rats 28 –30 . However, this does not reflect the range of potency on acid seen in the in vitro assay ( Figure 4), where the inhibition of acid by bosentan and Ro 48‐5695 at a 10 −4 M dose was about 50% and both compounds were at least 1000 times less potent on cAMP‐stimulated acid secretion than omeprazole.…”
Section: Discussionmentioning
confidence: 99%
“…After showing that bosentan inhibited WIRS‐stimulated acid secretion, they concluded that the antisecretory properties of bosentan are likely to be responsible for prevention of gastric damage 23 . This conclusion would make bosentan about three times less potent than omeprazole in attenuating gastric lesions in WIRS rats 28 –30 . However, this does not reflect the range of potency on acid seen in the in vitro assay ( Figure 4), where the inhibition of acid by bosentan and Ro 48‐5695 at a 10 −4 M dose was about 50% and both compounds were at least 1000 times less potent on cAMP‐stimulated acid secretion than omeprazole.…”
Section: Discussionmentioning
confidence: 99%